Doubled Standards of the Quality Assurance: Russia in the Bologna Process - Galina N. Motova (Высшее образование в России)
The article focuses on the role and the position of the Russian system of higher education in the Bologna process. The author dwells on the documents prepared for ministerial conferences including the Ministerial Conference in Paris held on May 24–25, 2018 and analyzes them from the position of inconsistency between the national educational policy in Russia and the Bologna process. Russia jointed the Bologna process fifteen years ago and made a commitment to provide integration in European higher education area. The results of this process may be treated differently, but such factors as magnitude, irreversibility, and incompleteness are evident. The report 2015 shows that Russia hasn’t implement the national qualifications framework, the implemented ECTS system is not entirely adequate to ECTS Users’ Guide, the problem of providing graduates with Diploma Supplement hasn’t yet been solved. The specifics of Russia’s approach to the problem of quality assurance are that there are both state accreditation and independent public procedures on academic recognition (accreditation agencies – ENQA members). The paper addresses quality assurance as a key tool of the integrating process.